A STUDY OF CORONARY HEART PATIENTSâ LIFESTYLE AT ZAINOEL ABIDIN HOSPITAL, BANDA ACEH, INDONESIA - Marniati, Marniati; Notoatmodjo, Soekidjo; Kasiman, Sutomo; Rochadi, R. Kintoko (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
About 40%of heart disease patients do not realize they have coronary heart disease (CHD). Based on the lifestyle of people in Aceh, there are several factors that can increase the CHD risk, such as smoking, coffee, fatty foods, stress, and lack of physical activity. Such a lifestyle has the potential to increase the risk of CHD, as evidenced statistical papers reportinghigh levels of CHD cases in Aceh. This study was aiamed toreview the patients lifestyle with coronary heart disease at Zainoel Abidin Hospital, Banda Aceh, Indonesia. This research is quantitative, with a case-control design.In April 2017, 206 cases of CHD and 206 non-PJK cases were analyzed, using patients medical record and a lifestyle questionnaire, in Zainoel Abidin Hospital. The result of bivariate analysis through a chi-square test showed that lifestyle factors related to CHD included diet, physical activity, smoking, coffee, and stress control (p <0,05). The results of the multivariate analysis with logistic regression showed that smoking is a lifestyle that remains a consistent as a risk factor for CHD. In addition, after interacting with other risk factors, stress control and coffee drinking habits become a protective factor of CHD. Smokers are twice risky to have CHD than nonsmokers. The influence of lifestyle on CHD is also determined by age and income factors. The research implications of this study offer various parties the opportunity to pursue an active involvement in preventive efforts against CHD.Keywords: Determinant, lifestyle, coronary heart disease, Zainoel Abidin Hospital